2022
DOI: 10.3389/fphar.2022.1016745
|View full text |Cite
|
Sign up to set email alerts
|

Shuangyu Tiaozhi decoction alleviates non-alcoholic fatty liver disease by improving lipid deposition, insulin resistance, and inflammation in vitro and in vivo

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases worldwide. Our previous studies have found that Shuangyu Tiaozhi Decoction (SYTZD) could produce an improvement in NAFLD-related indicators, but the underlying mechanism associated with this improvement remains unclear. The study aimed to investigate the potential mechanism of SYTZD against NAFLD through network pharmacology and experimental verification. The components of SYTZD and SYTZD drug containing serum were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…It was found that the key active compound isochlorogenic acid A may directly bind to VEGFA, IL-6, RELA, and MMP9, and exert a therapeutic effect by regulating the PI3K-Akt signaling pathway. Through analyzing Shuangyu Tiaozhi Decoction (SYTZD), Yin, et al (2022) also found that HIF-1α, FASN, GSK-3β, ESR1, mTOR, and VEGFA were the main targets for SYTZD to treat NAFLD. The main signaling pathways involved include the HIF-1 pathway, AMPK pathway, insulin resistance pathway thyroid hormone pathway, etc.…”
Section: Network Pharmacological Study On Non-alcoholic Fatty Liver D...mentioning
confidence: 99%
“…It was found that the key active compound isochlorogenic acid A may directly bind to VEGFA, IL-6, RELA, and MMP9, and exert a therapeutic effect by regulating the PI3K-Akt signaling pathway. Through analyzing Shuangyu Tiaozhi Decoction (SYTZD), Yin, et al (2022) also found that HIF-1α, FASN, GSK-3β, ESR1, mTOR, and VEGFA were the main targets for SYTZD to treat NAFLD. The main signaling pathways involved include the HIF-1 pathway, AMPK pathway, insulin resistance pathway thyroid hormone pathway, etc.…”
Section: Network Pharmacological Study On Non-alcoholic Fatty Liver D...mentioning
confidence: 99%
“…From these data, we conclude that along with IR and activation of TGF-β, the dysregulation of Wnt/β-catenin, NRIP1, Nrf2, SREBP-LXRα, PHBs, PPARs, and p53 play an important role in NASH pathogenesis. These findings caused an impulse in the discovery of novel biomarkers of NASH HCC and numerous chemopreventive and therapeutic studies with mTOR inhibitors in NAFLD/NASH/HCC [ 23 ].…”
Section: Signaling and Metabolic Pathways In The Regulation Of Nafld/...mentioning
confidence: 99%
“…From these data, we conclude that along with IR and activation of TGF-β, the dysregulation of Wnt/β-catenin, NRIP1, Nrf2, SREBP-LXRα, PHBs, PPARs, and p53 play an important role in NASH pathogenesis. These findings caused an impulse in the discovery of novel biomarkers of NASH HCC and numerous chemopreventive and therapeutic studies with mTOR inhibitors in NAFLD/NASH/HCC [23]. Through studies investigating mTOR biomarkers and inhibitors, it has been revealed that mTOR plays a critical role in regulating adipocyte and lipogenic marker genes, including PPAR and SREBP1c.…”
Section: Signaling and Metabolic Pathways In The Regulation Of Nafld/...mentioning
confidence: 99%